Modifikasi Pemanasan Dengan Motivasi Belajar Siswa Dalam Pembelajaran Pendidikan Jasmani - Yusup, Muhammad Fajri; Syafei, Muhammad Mury; -, Fahrudin (MANGGUREBE: Journal Physical Education, Health and Recreation, 2021)
This study aims to determine the relationship between heating modification and studentmotivation in learning physical education in class XI SMA Negeri 1 Jatibarang. This researchbelongs to the category of quantitative research with a correlational method. The population ofthis study were all students of class XI SMAN 1 Jatibarang, amounting to 117 people and totaledfive classes, each class numbering 23-24 people. The sampling technique used is probabilitysampling by means of simple random sampling, therefore the researcher takes a sample of 50% ofthe population or a number of 59 students to represent the entire population. Data were collectedby distributing questionnaires. The statistical analysis used was the correlation test, determinanttest, and t test. The correlation test results of 0.739 are included in the strong relationship level.Based on the results of the determinant test, it was obtained a determinant coefficient of 54.61%,which means that heating modification is an important factor in relation to learning motivation andthe remaining 45.39% is related to other factors. While the t test results obtained tcount 8,139 greater than ttable 2,002. In this case tcount is in the rejection area H0, so H0 is rejectedand H1 is accepted, meaning that there is a significant relationship between heating modificationand student learning motivation in learning physical education